Advances in precision epigenetic treatment for acute promyelocytic leukemia. Issue 3 (4th May 2019) - Pallavi, Rani; Mazzarella, Luca; Pelicci, Pier Giuseppe
ABSTRACT: Introduction : Acute promyelocytic leukemia (APL) is the foremost example of a neoplasm whose outcome has been radically changed by the identification of its underlying molecular mechanism and corresponding targeting drugs, namely All-Trans Retinoic Acid (ATRA) and Arsenic Trioxide (ATO). ATRA/ATO combination is able to cure the vast majority of APL patients. Still, a significant fraction of APL patients (high-risk subgroups, elderly and frail patients) still fail to achieve disease eradication. For these patients, additional treatment is required. Area covered : We reviewed current APL treatment and identified areas of unmet medical need. We provide an overview of the numerous preclinical studies pointing to a role for epigenetic factors in APL. Finally, we review clinical trials on epigenetic drugs in other myeloid neoplasms and the anecdotal clinical evidence in APL. Expert opinion : Despite an integral role of epigenetic factors in the development, pathogenesis, and emergence of drug resistance in APL, their therapeutic importance has not been fully explored clinically. Ironically, many epigenetic drugs, either in combination with all-trans-retinoic acid or chemotherapy, are in clinical trials for myeloid neoplasms different from APLs. These drugs may play a role for specific APL patient populations.